CEO’S GENDER AND EARNINGS MANAGEMENT - Debbianita, Debbianita; Prayogo, Enny; Agustina, Lidya; Erwan, Erwan (2021)
The aim of this study is to see how the gender of CEO affects earnings management in manufacturing companies that were listed on Indonesia Stock Exchange in 2018. Explanatory analysis was used in this study, and judgment sampling method was used to determine the sample size. The research hypothesis was checked with SPSS version 20 and the result shows that The gender of the CEO has no effect on earnings management.